The efficacy and safety of targeted agents approved for advanced non-small cell lung cancer in China: a cross-sectional analysis - Xingxian Luo; Xin Du; Xufeng Lv; Lizong Li; Lin Huang (The Lancet Regional Health. Western Pacific)
Background: Lung cancer, as the disease with the highest mortality and incidence rate in China, has emerged as one of the most heavily burdened diseases. Recently, China has approved several targeted cancer agents for advanced first-line non-small cell lung cancer (NSCLC), including small molecule drugs and immune checkpoint inhibitors, which are critical for improving overall survival of patients. However, no studies have systematically evaluated the efficacy and safety of these targeted agents with different mechanisms of action. Methods: The targeted cancer drugs approved for first-line treatment of advanced non-small cell lung cancer (NSCLC) in China were included between January 1, 2010, and October 1, 2024, using the National Medical Products Administration database. The key efficacy and safety outcomes were extracted from the pivotal clinical trials that supported the approval of these drugs, including progression-free survival (PFS), overall survival (OS), and treatment-related serious adverse events (SAE) and deaths. This analysis focused on randomized controlled trials, excluding single-arm studies. A meta-analysis using a random-effects model was conducted to summarize these outcomes based on different therapeutic targets. Findings: A total of 18 new molecular entities (24 indications) have been approved in China for the first-line treatment of advanced NSCLC including 8 PD1/PDL1 inhibitors, 6 ALK inhibitors, and 4 EGFR inhibitors. Each indication was supported by one randomized controlled trial. The pooled hazard ratios (HR) for PFS were 0.52 (95% CI: 0.49, 0.56) for PD1/PDL1 inhibitors, 0.47 (95% CI: 0.41, 0.54) for ALK inhibitors, and 0.49 (95% CI: 0.43, 0.56) for EGFR inhibitors. For overall survival (OS), the pooled HRs were 0.65 (95% CI: 0.59, 0.72), 0.75 (95% CI: 0.60, 0.94), and 0.77 (95% CI: 0.66, 0.91), respectively. These targeted therapies extended the median OS by 7.1 months (IQR: 5.1, 9.5). In terms of safety, the pooled rate of treatment-related serious adverse events was 28% (95% CI: 23%, 34%) for PD1/PDL1 inhibitors, 14% (95% CI: 7%, 28%) for ALK inhibitors, and 8% (95% CI: 5%, 12%) for EGFR inhibitors. Treatment-related mortality was 3% (95% CI: 2%, 4%) for PD1/PDL1 inhibitors, 0% (95% CI: 0%, 2%) for ALK inhibitors, and 1% (95% CI: 0%, 9%) for EGFR inhibitors. Interpretation: The approved targeted cancer agents in China significantly prolonged the overall survival of advanced NSCLC. It appears that PD-1/PDL-1 reduces the risk of patient death more than ALK and EGFR inhibitors, but simultaneously faces more severe adverse effects.